Mitotoxicity in distal symmetrical sensory peripheral neuropathies - Bennett, Gary J. (Nat Rev Neurol, 2014)
Chronic distal symmetrical sensory peripheral neuropathy is a common neurological complication of cancer chemotherapy, HIV treatment and diabetes. Although aetiology-specific differences in presentation are evident, the clinical signs and symptoms of these neuropathies are clearly similar. Data from animal models of neuropathic pain suggest that the similarities have a common cause: mitochondrial dysfunction in primary afferent sensory neurons. Mitochondrial dysfunction is caused by mitotoxic effects of cancer chemotherapeutic drugs of several chemical classes, HIV-associated viral proteins, and nucleoside reverse transcriptase inhibitor treatment, as well as the (possibly both direct and indirect) effects of excess glucose. The mitochondrial injury results in a chronic neuronal energy deficit, which gives rise to spontaneous nerve impulses and a compartmental neuronal degeneration that is first apparent in the terminal receptor arbor—that is, intraepidermal nerve fibres—of cutaneous afferent neurons. Preliminary data suggest that drugs that prevent mitochondrial injury or improve mitochondrial function could be useful in the treatment of these conditions.